A porous carbon sphere-loaded bismuth oxyhalide hybrid material and its application in photocatalytic degradation of heavy metal salts
By using porous carbon sphere-supported bismuth oxyhalide hybrid materials, the problem of insufficient catalytic efficiency in the photocatalytic degradation of heavy metal salts is solved, and high-efficiency photocatalytic degradation with excellent light absorption capacity in both ultraviolet and visible light regions is achieved. Effect.
Patent Information
- Application Number
- CN202411554721.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-04
AI Technical Summary
In the photocatalytic degradation of heavy metal salts, existing photocatalytic degradation of heavy metal salts, the short lifespan, the low concentration of photogenerated carriers, and the high electron/hole recombination degree, resulting in insufficient catalytic efficiency.
Using porous carbon sphere-loaded bismuth oxyhalide hybrid materials, different types and different element contents are prepared through a simple preparation method to improve their light absorption capacity in the ultraviolet and visible light regions.
It has achieved excellent light absorption capacity in both ultraviolet and visible light regions, low cost, wide applicability, high cleaning efficiency and mild cleaning conditions, and is suitable for photocatalytic degradation treatment of large-scale heavy metal salts.
Smart Images

Figure CN119076023B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of disinfection materials, and specifically relates to a porous carbon ball-loaded bismuth oxyhalide hybrid material and its application in the photocatalytic degradation of heavy metal salts. Background Art
[0002] With the development of urbanization and industrialization, water pollution poses an increasing threat to human health. Phenol-containing wastewater generated by various industries is a major source of water pollution. Phenol pollutants in water bodies are toxic, carcinogenic and stable, so the degradation of phenolic pollutants is an urgent problem to be solved. Photocatalytic degradation is a commonly used technology for degrading pollutants. Due to its green and pollution-free nature, it is a very promising technology and has attracted widespread attention. Under the irradiation of sunlight, photogenerated electrons and holes will combine with dissolved oxygen molecules or water molecules in water to produce ·O2 - , OH or O 1 / 2 Active free radicals such as ions are generated by oxidation-reduction reactions with pollutants to degrade them. However, current photocatalysts have the disadvantages of short lifespan, low concentration of photogenerated carriers, and high electron / hole recombination, which lead to insufficient catalytic efficiency and limit the development of photocatalysts.
[0003] Among the reported visible light-driven photocatalysts, BiOBr has attracted extensive attention due to its convenient halogen element tunability, photochemical stability, and layered structure for decomposing various organic pollutants in water. For example, Huo Yuning et al. from the Shanghai Key Laboratory of Rare Earth Functional Materials assembled layered flower-like BiOBr microspheres by a solvothermal method. Flower-like BiOBr has high photocatalytic activity for the degradation of rhodamine B. However, the original BiOBr has the inherent defect of rapid recombination of photogenerated electron-hole pairs, which greatly limits its practical application, and there are few reports on the catalytic degradation of heavy metal salts by BiOBr. In order to improve the electron-hole separation efficiency of BiOBr photocatalysts and thus improve their catalytic performance under visible light irradiation, domestic and foreign scholars have used methods such as doping, precious metal deposition, and semiconductor composite to modify BiOBr, but these methods have problems such as high research cost and immature technology. Therefore, the development of a class of photocatalysts with simple preparation methods, low addition amount, strong catalytic ability and high catalytic efficiency has become an urgent need and goal in the catalytic industry and related fields such as water pollutant degradation treatment. Summary of the invention
[0004] In view of the deficiencies in the above-mentioned prior art, the present invention provides a porous carbon sphere-loaded bismuth oxyhalide hybrid material and its application in the photocatalytic degradation of heavy metal salts. The preparation method of the porous carbon sphere-loaded bismuth oxyhalide hybrid material of the present invention is relatively simple, and hybrid disinfection materials of different types and different element contents can be prepared by structural regulation, which is suitable for the photocatalytic degradation treatment of different heavy metal salts. In addition, compared with traditional bismuth oxyhalides, the hybrid material of the present invention has excellent light absorption capacity in both ultraviolet and visible light regions. The hybrid material of the present invention has the advantages of low cost, wide applicability, high disinfection efficiency, mild disinfection conditions, etc., and is therefore more suitable for large-scale disinfection and disposal of heavy metal salts, especially disinfection treatment of water pollution.
[0005] The porous carbon sphere-loaded bismuth oxyhalide hybrid material of the present invention has a chemical formula as shown in the following formula (I):
[0006]
[0007] In formula (I), the constituent element of X is any one of the four halogens of fluorine (F), chlorine (Cl), bromine (Br), and iodine (I).
[0008] The method for preparing the porous carbon sphere-supported bismuth oxyhalide hybrid material of the present invention comprises the following steps:
[0009] Step 1: At room temperature, add Tris-HCl buffer (pH=8.5) to a certain mass of deionized water, then add silica (SiO2) microspheres (size 50-500 nm), and stir ultrasonically for a certain period of time.
[0010] Step 2: Slowly add a certain mass of ammonia water and a certain mass of dopamine hydrochloride aqueous solution into the mixture obtained in step 1, stir and react for a certain time, filter, wash and dry to obtain an intermediate product, i.e., dopamine-encapsulated silica microspheres (SiO2@PDA).
[0011] Step 3: Under the protection of inert gas, use a tubular furnace to heat the SiO2@PDA obtained in step 2 to a certain temperature at a certain heating rate and keep it warm for a certain time; then add the obtained product to a hydrofluoric acid aqueous solution of a certain concentration, stir it at room temperature for a certain time, filter, wash and dry to obtain an intermediate product, namely carbon spheres (C).
[0012] Step 4: At room temperature, add a certain amount of bismuth nitrate pentahydrate (Bi(NO3)3·5H2O) to the ethylene glycol solution of hexadecyltrimethylammonium bromide (CTAB) and stir for a certain time. Then add the carbon spheres obtained in step 3 and stir and ultrasonicate for a certain time.
[0013] Step 5: Add a certain mass of potassium salt KX to the mixture obtained in step 4, stir for a certain period of time, transfer the mixture to a high-pressure reactor, heat for reaction, and filter, wash and dry after the reaction to obtain the target product.
[0014] In step 1, the mass ratio of silica microspheres, Tris-HCl buffer and deionized water is 1: 7.88: 500.
[0015] In step 1, the ultrasonic stirring time is controlled at 5-7h.
[0016] In step 2, the mass ratio of silica microspheres, ammonia water and dopamine hydrochloride aqueous solution is 1: 5: 500. Among them, the mass fraction of ammonia water is 25%-28%, and the mass fraction of dopamine hydrochloride aqueous solution is 0.2%.
[0017] In step 2, the reaction time is 22-24 hours.
[0018] In step 3, the heating rate of the tubular furnace is 5°C / min, the reaction temperature is 550°C, and the holding time is 2 h.
[0019] In step 3, the mass ratio of SiO2@PDA to hydrofluoric acid aqueous solution is 1:100-200, wherein the mass fraction of hydrofluoric acid aqueous solution is 20%, and the stirring reaction time at room temperature is 12-24h.
[0020] In step 4, the mass fraction of the ethylene glycol solution of CTAB is 4.8%.
[0021] In step 5, the potassium salt KX is selected from any one of potassium fluoride (KF), potassium chloride (KCl), potassium bromide (KBr), and potassium iodide (KI).
[0022] In steps 4 and 5, the molar ratio of potassium salt to bismuth nitrate pentahydrate is 1: 1. The mass ratio of potassium salt, carbon spheres, bismuth nitrate pentahydrate and CTAB ethylene glycol solution is 1: 2.35-4.70: 2.92-8.23: 317.3.
[0023] In step 4, the stirring reaction time is 30 min, and the stirring ultrasonic reaction time is 30-60 min.
[0024] In step 5, the stirring reaction time is 10-30 minutes. The reaction temperature of the high-pressure reactor is 160-180° C., and the reaction time is 6-12 hours.
[0025] The inert gas is any one of nitrogen, argon or helium.
[0026] The invention discloses an application of the porous carbon sphere-loaded bismuth oxyhalide hybrid material as a cleaning material in the photocatalytic degradation of heavy metal salts.
[0027] The heavy metal salts include heavy metal salts such as Cr(VI), Cd(II), and Pb(II).
[0028] The pH value of the catalytic degradation system was adjusted to 2.
[0029] The concentration of the heavy metal salt is 5-20 mg / L, more preferably 5-10 mg / L, and the concentration is calculated as heavy metal element.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] 1. The porous carbon sphere-loaded bismuth oxyhalide hybrid decontamination material provided by the present invention has a simple preparation method, and can be used to prepare hybrid decontamination materials of different types and with different element contents through structural regulation, and is suitable for photocatalytic degradation of heavy metal salts. In addition, compared with traditional bismuth oxyhalide, the hybrid decontamination material prepared by the present invention has excellent light absorption capacity in both ultraviolet and visible light regions. The hybrid decontamination material described in the present invention has the advantages of low cost, wide applicability, high decontamination efficiency, and mild decontamination conditions.
[0032] 2. The porous carbon sphere-loaded bismuth oxyhalide hybrid disinfection material provided by the present invention has a "sheet-sphere" composite structure, which increases the specific surface area, effectively increases the contact area with pollutants, and improves the disinfection efficiency.
[0033] 3. The hybrid decontamination material provided by the present invention can conveniently regulate the structure of the hybrid decontamination material by changing the type of bismuth oxyhalide. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0035] Figure 1 The scanning electron microscope (SEM) images of the samples in Comparative Example 1 (a), Comparative Example 2 (b), and Example 3 (c) of the present invention are shown.
[0036] Figure 2 Transmission electron microscope (TEM) images of the samples in Comparative Example 1 (a), Comparative Example 2 (b), and Example 3 (c) of the present invention.
[0037] Figure 3 These are the UV-visible diffuse reflectance spectrum images of the samples in Comparative Example 1, Comparative Example 3 and Example 3 of the present invention.
[0038] Figure 4 The figure is the decontamination performance curve of the BiOBr@C hybrid decontamination material for Cr(VI) ions at different pH values (pH = 2, 3, 6) in Example 3 of the present invention.
[0039] Figure 5 : This is the decontamination performance curve of the BiOBr@C hybrid decontamination material in Example 3 of the present invention for different Cr(VI) ion concentrations (5 mg / L, 10 mg / L and 20 mg / L).
[0040] Figure 6 The decontamination performance curves of the samples in Comparative Example 1, Comparative Example 2 and Example 3 of the present invention for Cr(VI) ions are shown.
[0041] Figure 7 These are the experimental results of the decontamination stability test of the BiOBr@C hybrid decontamination material against Cr(VI) ions in Example 3. DETAILED DESCRIPTION
[0042] In order to further illustrate the technical solution of the present invention, the preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention. Based on the examples in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. Embodiment 1:
[0043] 1. At room temperature, accurately weigh 7.88 parts of Tris-HCl buffer (pH = 8.5), add it to 500 parts of deionized water, then add 1 part of accurately weighed silica (SiO2) microspheres, and stir ultrasonically for 6 hours. Subsequently, slowly add 5 parts of 25% ammonia water and 500 parts of 0.2% dopamine hydrochloride aqueous solution, stir magnetically for 24 hours, filter and wash with deionized water and ethanol, and dry in an oven at 60°C to obtain dopamine-coated silica microspheres (SiO2@PDA).
[0044] 2. Under nitrogen protection, accurately weigh 1 part of SiO2@PDA and place it in a tube furnace, heat it to 550℃ at a heating rate of 5℃ / min, and keep it warm for 2 hours. Then add 100 parts of 20% hydrofluoric acid aqueous solution accurately weighed, stir magnetically at room temperature for 12 hours, filter and wash with deionized water, and dry in an oven at 60℃ to obtain carbon spheres (C).
[0045] 3. At room temperature, accurately weigh 8.23 parts of bismuth nitrate pentahydrate (Bi(NO3)3·5H2O) and add it to 317.3 parts of ethylene glycol solution of hexadecyltrimethylammonium bromide with a mass fraction of 4.8%, and stir for 30 min. Then, accurately weigh 2.35 parts of C and stir and ultrasonicate for 30 min. Subsequently, accurately weigh 1 part of potassium fluoride (KF) and stir for 10 min, wherein the molar ratio of KF to Bi(NO3)3·5H2O is 1:1. Transfer the mixed solution to a high-pressure reactor, heat to 160°C, react for 6 h, filter and wash with deionized water and ethanol, and dry in an oven at 60°C to obtain the target product a. Embodiment 2:
[0046] 1. At room temperature, accurately weigh 7.88 parts of Tris-HCl buffer (pH = 8.5), add it to 500 parts of deionized water, then add 1 part of accurately weighed silica (SiO2) microspheres, and stir ultrasonically for 6 hours. Subsequently, slowly add 5 parts of 25% ammonia water and 500 parts of 0.2% dopamine hydrochloride aqueous solution, stir magnetically for 24 hours, filter and wash with deionized water and ethanol, and dry in an oven at 60°C to obtain dopamine-coated silica microspheres (SiO2@PDA).
[0047] 2. Under nitrogen protection, accurately weigh 1 part of SiO2@PDA and place it in a tube furnace, heat it to 550℃ at a heating rate of 5℃ / min, and keep it warm for 2 hours. Then add 100 parts of 20% hydrofluoric acid aqueous solution accurately weighed, stir magnetically at room temperature for 12 hours, filter and wash with deionized water, and dry in an oven at 60℃ to obtain carbon spheres (C).
[0048] 3. At room temperature, accurately weigh 6.51 parts of bismuth nitrate pentahydrate (Bi(NO3)3·5H2O) and add it to 317.3 parts of ethylene glycol solution of hexadecyltrimethylammonium bromide with a mass fraction of 4.8%, and stir for 30 min. Then, accurately weigh 2.35 parts of C and stir and ultrasonicate for 30 min. Subsequently, accurately weigh 1 part of potassium chloride (KCl) and stir for 10 min, wherein the molar ratio of KCl to Bi(NO3)3·5H2O is 1:1. Transfer the mixed solution to a high-pressure reactor, heat to 160°C, react for 6 h, filter and wash with deionized water and ethanol, and dry in an oven at 60°C to obtain the target product b. Embodiment 3:
[0049] 1. At room temperature, accurately weigh 7.88 parts of Tris-HCl buffer (pH = 8.5), add it to 500 parts of deionized water, then add 1 part of accurately weighed silica (SiO2) microspheres, and stir ultrasonically for 6 hours. Subsequently, slowly add 5 parts of 25% ammonia water and 500 parts of 0.2% dopamine hydrochloride aqueous solution, stir magnetically for 24 hours, filter and wash with deionized water and ethanol, and dry in an oven at 60°C to obtain dopamine-coated silica microspheres (SiO2@PDA).
[0050] 2. Under nitrogen protection, accurately weigh 1 part of SiO2@PDA and place it in a tube furnace, heat it to 550℃ at a heating rate of 5℃ / min, and keep it warm for 2 hours. Then add 100 parts of 20% hydrofluoric acid aqueous solution accurately weighed, stir magnetically at room temperature for 12 hours, filter and wash with deionized water, and dry in an oven at 60℃ to obtain carbon spheres (C).
[0051] 3. At room temperature, accurately weigh 4.08 parts of bismuth nitrate pentahydrate (Bi(NO3)3·5H2O) and add it to 317.3 parts of ethylene glycol solution of hexadecyltrimethylammonium bromide with a mass fraction of 4.8%, and stir for 30 min. Then, accurately weigh 2.35 parts of C and stir and ultrasonicate for 30 min. Subsequently, accurately weigh 1 part of potassium bromide (KBr) and stir for 10 min, wherein the molar ratio of KBr to Bi(NO3)3·5H2O is 1:1. Transfer the mixed solution to a high-pressure reactor, heat to 160°C, react for 6 h, filter and wash with deionized water and ethanol, and dry in an oven at 60°C to obtain the target product c. Embodiment 4:
[0052] 1. At room temperature, accurately weigh 7.88 parts of Tris-HCl buffer (pH = 8.5), add it to 500 parts of deionized water, then add 1 part of accurately weighed silica (SiO2) microspheres, and stir ultrasonically for 6 hours. Subsequently, slowly add 5 parts of 25% ammonia water and 500 parts of 0.2% dopamine hydrochloride aqueous solution, stir magnetically for 24 hours, filter and wash with deionized water and ethanol, and dry in an oven at 60°C to obtain dopamine-coated silica microspheres (SiO2@PDA).
[0053] 2. Under nitrogen protection, accurately weigh 1 part of SiO2@PDA and place it in a tube furnace, heat it to 550℃ at a heating rate of 5℃ / min, and keep it warm for 2 hours. Then add 100 parts of 20% hydrofluoric acid aqueous solution accurately weighed, stir magnetically at room temperature for 12 hours, filter and wash with deionized water, and dry in an oven at 60℃ to obtain carbon spheres (C).
[0054] 3. At room temperature, accurately weigh 2.92 parts of bismuth nitrate pentahydrate (Bi(NO3)3·5H2O) and add it to 317.3 parts of ethylene glycol solution of hexadecyltrimethylammonium bromide with a mass fraction of 4.8%, and stir for 30 min. Then, accurately weigh 2.35 parts of C and stir and ultrasonicate for 30 min. Subsequently, accurately weigh 1 part of potassium iodide (KI) and stir for 10 min, wherein the molar ratio of KI to Bi(NO3)3·5H2O is 1:1. Transfer the mixed solution to a high-pressure reactor, heat to 160°C, react for 6 h, filter and wash with deionized water and ethanol, and dry in an oven at 60°C to obtain the target product d. Embodiment 5:
[0055] 1. At room temperature, accurately weigh 7.88 parts of Tris-HCl buffer (pH = 8.5), add it to 500 parts of deionized water, then add 1 part of accurately weighed silica (SiO2) microspheres, and stir ultrasonically for 6 hours. Subsequently, slowly add 5 parts of 25% ammonia water and 500 parts of 0.2% dopamine hydrochloride aqueous solution, stir magnetically for 24 hours, filter and wash with deionized water and ethanol, and dry in an oven at 60°C to obtain dopamine-coated silica microspheres (SiO2@PDA).
[0056] 2. Under nitrogen protection, accurately weigh 1 part of SiO2@PDA and place it in a tube furnace, heat it to 550℃ at a heating rate of 5℃ / min, and keep it warm for 2 hours. Then add 100 parts of 20% hydrofluoric acid aqueous solution accurately weighed, stir magnetically at room temperature for 12 hours, filter and wash with deionized water, and dry in an oven at 60℃ to obtain carbon spheres (C).
[0057] 3. At room temperature, accurately weigh 4.08 parts of bismuth nitrate pentahydrate (Bi(NO3)3·5H2O) and add it to 317.3 parts of ethylene glycol solution of hexadecyltrimethylammonium bromide with a mass fraction of 4.8%, and stir for 30 min. Then, accurately weigh 4.7 parts of C and stir and ultrasonicate for 30 min. Subsequently, accurately weigh 1 part of potassium bromide (KBr) and stir for 10 min, wherein the molar ratio of KBr to Bi(NO3)3·5H2O is 1:1. Transfer the mixed solution to a high-pressure reactor, heat to 160°C, react for 6 h, filter and wash with deionized water and ethanol, and dry in an oven at 60°C to obtain the target product e. Embodiment 6:
[0058] 1. At room temperature, accurately weigh 7.88 parts of Tris-HCl buffer (pH = 8.5), add it to 500 parts of deionized water, then add 1 part of accurately weighed silica (SiO2) microspheres, and stir ultrasonically for 6 hours. Subsequently, slowly add 5 parts of 25% ammonia water and 500 parts of 0.2% dopamine hydrochloride aqueous solution, stir magnetically for 24 hours, filter and wash with deionized water and ethanol, and dry in an oven at 60°C to obtain dopamine-coated silica microspheres (SiO2@PDA).
[0059] 2. Under nitrogen protection, accurately weigh 1 part of SiO2@PDA and place it in a tube furnace, heat it to 550℃ at a heating rate of 5℃ / min, and keep it warm for 2 hours. Then add 100 parts of 20% hydrofluoric acid aqueous solution accurately weighed, stir magnetically at room temperature for 12 hours, filter and wash with deionized water, and dry in an oven at 60℃ to obtain carbon spheres (C).
[0060] 3. At room temperature, accurately weigh 4.08 parts of bismuth nitrate pentahydrate (Bi(NO3)3·5H2O) and add it to 317.3 parts of ethylene glycol solution of hexadecyltrimethylammonium bromide with a mass fraction of 4.8%, and stir for 30 min. Then, accurately weigh 2.35 parts of C and stir and ultrasonicate for 30 min. Subsequently, accurately weigh 1 part of potassium bromide (KBr) and stir for 10 min, wherein the molar ratio of KBr to Bi(NO3)3·5H2O is 1:1. Transfer the mixed solution to a high-pressure reactor, heat to 160°C, react for 12 h, filter and wash with deionized water and ethanol, and dry in an oven at 60°C to obtain the target product f. Embodiment 7:
[0061] 1. At room temperature, accurately weigh 7.88 parts of Tris-HCl buffer (pH = 8.5), add it to 500 parts of deionized water, then add 1 part of accurately weighed silica (SiO2) microspheres, and stir ultrasonically for 6 hours. Subsequently, slowly add 5 parts of 25% ammonia water and 500 parts of 0.2% dopamine hydrochloride aqueous solution, stir magnetically for 24 hours, filter and wash with deionized water and ethanol, and dry in an oven at 60°C to obtain dopamine-coated silica microspheres (SiO2@PDA).
[0062] 2. Under nitrogen protection, accurately weigh 1 part of SiO2@PDA and place it in a tube furnace, heat it to 550℃ at a heating rate of 5℃ / min, and keep it warm for 2 hours. Then add 100 parts of 20% hydrofluoric acid aqueous solution accurately weighed, stir magnetically at room temperature for 12 hours, filter and wash with deionized water, and dry in an oven at 60℃ to obtain carbon spheres (C).
[0063] 3. At room temperature, accurately weigh 4.08 parts of bismuth nitrate pentahydrate (Bi(NO3)3·5H2O) and add it to 317.3 parts of ethylene glycol solution of hexadecyltrimethylammonium bromide with a mass fraction of 4.8%, and stir for 30 min. Then, accurately weigh 2.35 parts of C and stir and ultrasonicate for 30 min. Subsequently, accurately weigh 1 part of potassium bromide (KBr) and stir for 10 min, wherein the molar ratio of KBr to Bi(NO3)3·5H2O is 1:1. Transfer the mixed solution to a high-pressure reactor, heat to 180°C, react for 6 h, filter and wash with deionized water and ethanol, and dry in an oven at 60°C to obtain the target product g. Embodiment 8:
[0064] 1. At room temperature, accurately weigh 7.88 parts of Tris-HCl buffer (pH = 8.5), add it to 500 parts of deionized water, then add 1 part of accurately weighed silica (SiO2) microspheres, and stir ultrasonically for 6 hours. Subsequently, slowly add 5 parts of 25% ammonia water and 500 parts of 0.2% dopamine hydrochloride aqueous solution, stir magnetically for 24 hours, filter and wash with deionized water and ethanol, and dry in an oven at 60°C to obtain dopamine-coated silica microspheres (SiO2@PDA).
[0065] 2. Under nitrogen protection, accurately weigh 1 part of SiO2@PDA and place it in a tube furnace, heat it to 550℃ at a heating rate of 5℃ / min, and keep it warm for 2 hours. Then add 100 parts of 20% hydrofluoric acid aqueous solution accurately weighed, stir magnetically at room temperature for 12 hours, filter and wash with deionized water, and dry in an oven at 60℃ to obtain carbon spheres (C).
[0066] 3. At room temperature, accurately weigh 4.08 parts of bismuth nitrate pentahydrate (Bi(NO3)3·5H2O) and add it to 317.3 parts of ethylene glycol solution of hexadecyltrimethylammonium bromide with a mass fraction of 4.8%, and stir for 30 min. Then, accurately weigh 2.35 parts of C and stir and ultrasonicate for 30 min. Subsequently, accurately weigh 1 part of potassium bromide (KBr) and stir for 10 min, wherein the molar ratio of KBr to Bi(NO3)3·5H2O is 1:1. Transfer the mixed solution to a high-pressure reactor, heat to 180°C, react for 12 h, filter and wash with deionized water and ethanol, and dry in an oven at 60°C to obtain the target product h.
[0067] Comparative Example 1:
[0068] At room temperature, 4.08 parts of bismuth nitrate pentahydrate (Bi(NO3)3·5H2O) were accurately weighed and added to 317.3 parts of ethylene glycol solution of hexadecyltrimethylammonium bromide (4.8% by mass) and stirred for 30 min. Then, 1 part of potassium bromide (KBr) was accurately weighed and stirred for 10 min, wherein the molar ratio of KBr to Bi(NO3)3·5H2O was 1:1. The mixed solution was transferred to an autoclave, heated to 160°C, reacted for 6 h, filtered, washed with deionized water and ethanol, and dried in an oven at 60°C to obtain BiOBr.
[0069] Comparative Example 2:
[0070] 1. At room temperature, accurately weigh 7.88 parts of Tris-HCl buffer (pH = 8.5), add it to 500 parts of deionized water, then add an accurately weighed part of silica (SiO2) microspheres, and stir ultrasonically for 6 hours. Subsequently, slowly add 5 parts of 25% ammonia water and 500 parts of 0.2% dopamine hydrochloride aqueous solution, stir magnetically for 24 hours, filter and wash with deionized water and ethanol, and dry in a 60 ° C oven to obtain dopamine-coated silica microspheres (PDA@SiO2).
[0071] 2. Under nitrogen protection, accurately weigh 1 part of SiO2@PDA and place it in a tube furnace, heat it to 550℃ at a heating rate of 5℃ / min, and keep it warm for 2 hours. Then add 100 parts of 20% hydrofluoric acid aqueous solution accurately weighed, stir mechanically at room temperature for 12 hours, filter and wash with deionized water, and dry in an oven at 60℃ to obtain carbon spheres (C).
[0072] Comparative Example 3:
[0073] 1. At room temperature, accurately weigh 7.88 parts of Tris-HCl buffer (pH = 8.5), add it to 500 parts of deionized water, then add 1 part of accurately weighed silica (SiO2) microspheres, and stir ultrasonically for 6 hours. Subsequently, slowly add 5 parts of 25% ammonia water and 500 parts of 0.2% dopamine hydrochloride aqueous solution, stir magnetically for 24 hours, filter and wash with deionized water and ethanol, and dry in an oven at 60°C to obtain dopamine-coated silica microspheres (SiO2@PDA).
[0074] 2. At room temperature, accurately weigh 4.08 parts of bismuth nitrate pentahydrate (Bi(NO3)3·5H2O) and add it to 317.3 parts of ethylene glycol solution of hexadecyltrimethylammonium bromide with a mass fraction of 4.8%, and stir for 30 min. Then, accurately weigh 2.35 parts of SiO2 microspheres and stir and ultrasonicate for 30 min. Subsequently, accurately weigh 1 part of potassium bromide (KBr) and stir for 10 min, where the molar ratio of KBr to Bi(NO3)3·5H2O is 1:1. Transfer the mixed solution to a high-pressure reactor, heat to 160℃, react for 6 h, filter and wash with deionized water and ethanol, and dry in an oven at 60℃ to obtain BiOBr@SiO2.
[0075] The performance test results of the products obtained in the above embodiments and comparative examples are as follows:
[0076] The scanning electron microscope (SEM) images of the samples in Comparative Example 1, Comparative Example 2 and Example 3 are as follows: Figure 1 As shown. BiOBr (Comparative Example 1) presents a typical multilayer structure ( Figure 1 The width of the lamellae is relatively large, all at the micrometer level. However, C (Comparative Example 2) is a relatively regular spherical structure ( Figure 1 Figure b), with a diameter of about 200 nm. The BiOBr@C (Example 3) hybrid material is a typical composite "sheet-sphere" structure ( Figure 1 Figure c in the middle) shows the successful composite of BiOBr microsheets and C nanospheres. The SEM results illustrate the structural characteristics of the BiOBr@C hybrid decontamination material and prove its successful synthesis.
[0077] The transmission electron microscope (TEM) images of the samples in Comparative Example 1, Comparative Example 2 and Example 3 are as follows: Figure 2 As shown. BiOBr (Comparative Example 1) exhibits the structural characteristics of coexistence of single-layer and multi-layer sheets ( Figure 2 (a in the middle), which is consistent with the test results of SEM. C (Comparative Example 2) is a stacked sphere structure ( Figure 2 (b), which is consistent with the SEM test results. In the TEM image of the BiOBr@C hybrid decontamination material, the composite "sheet-sphere" structure and the stacking of sheets and spheres are clearly visible. The TEM results further explored the structural characteristics of the BiOBr@C hybrid decontamination material and proved its successful synthesis.
[0078] The UV-visible diffuse reflectance spectra of the samples in Comparative Example 1, Comparative Example 3 and Example 3 are shown in FIG. Figure 3As shown. For BiOBr (Comparative Example 1) and BiOBr@SiO2 (Comparative Example 3), they showed relatively high absorbance and strong light absorption capacity in the ultraviolet light region (200-400 nm), but their light absorption capacity in the visible light region (400-800 nm) dropped sharply. Through hybridization, although the light absorption capacity of BiOBr@C in the ultraviolet light region decreased, it showed strong light absorption capacity in the visible light region. The UV-visible diffuse reflectance spectrum proves that the BiOBr@C hybrid disinfectant material has a strong absorption capacity in the visible light region, which is conducive to the improvement of its photocatalytic efficiency under visible light.
[0079] The decontamination performance curves of the BiOBr@C hybrid decontamination material for Cr(VI) ions at different pH values (pH = 2, 3, 6) in Example 3 are shown in FIG. Figure 4 As shown. The dosage of BiOBr@C hybrid disinfection material is 50 mg, and the concentration of Cr(VI) ions is 10 mg / L. As the pH value increases, the disinfection effect of BiOBr@C hybrid disinfection material on Cr(VI) ions is significantly reduced. When pH=2, Cr(VI) ions are completely degraded in 36 h; when pH=3, Cr(VI) ions are degraded by 39% in 36 h; when pH=6, Cr(VI) ions are only degraded by 19% in 36 h. This is because when the pH is between 2 and 6, the main form of Cr(VI) is Cr2O7 − or HCrO4 − When the pH is low, the reduction product is Cr 3+ The zeta potential of the hybrid disinfection material surface is positive, which is similar to Cr 3+ There is electrostatic repulsion, and the reduction product will leave the reaction site. As the pH value increases, the proportion of the reduction product Cr(OH)3 increases, and the zeta potential on the surface of the hybrid disinfection material becomes negative, which has an electrostatic adsorption effect on the reduction product, reducing the utilization efficiency of the reaction site.
[0080] The decontamination performance curves of the BiOBr@C hybrid decontamination material in Example 3 for different Cr(VI) ion concentrations (5 mg / L, 10 mg / L and 20 mg / L) are shown in FIG. Figure 5As shown. The dosage of BiOBr@C hybrid decontamination material is 50 mg, and the pH value of the solution is 2. As the concentration of Cr(VI) ions increases, the decontamination effect of BiOBr@C hybrid decontamination material on Cr(VI) ions decreases significantly. When the concentration of Cr(VI) ions is 5 mg / L, Cr(VI) ions are completely degraded in 24 h; when the concentration of Cr(VI) ions is 10 mg / L, Cr(VI) ions are completely degraded in 36 h; when the concentration of Cr(VI) ions is 20 mg / L, Cr(VI) ions are degraded by 43% in 36 h. This is because the catalytic sites on the surface of BiOBr@C hybrid decontamination material are limited. When the concentration of Cr(VI) ions is too high, the catalytic sites reach a saturated state and its decontamination efficiency cannot be further improved.
[0081] The decontamination performance curves of the samples in Comparative Example 1, Comparative Example 2 and Example 3 for Cr(VI) ions are as follows: Figure 6 As shown. The dosage of each sample was 50 mg, the pH value of the solution was 2, and the concentration of Cr(VI) ions was 5 mg / L. The decontamination efficiency of BiOBr@C hybrid decontamination material was the best, and Cr(VI) ions were completely degraded at 24 h. The decontamination efficiency of BiOBr was second, and Cr(VI) ions were completely degraded at 36 h. When porous carbon spheres were used as decontamination materials, although the decrease in Cr(VI) ion concentration in the early and middle stages was better than that of the BiOBr group, the Cr(VI) ion concentration almost stopped decreasing after 30 h. This is because the porous carbon spheres mainly played an adsorption role on Cr(VI) ions, and the adsorption process reached saturation equilibrium at 30 h.
[0082] The experimental results of the decontamination stability of the BiOBr@C hybrid decontamination material against Cr(VI) ions in Example 3 are as follows: Figure 7 As shown. The dosage of BiOBr@C hybrid decontamination material was 50 mg, the pH value of the solution was 2, the concentration of Cr(VI) ions was 5 mg / L (C0), and the experimental time was 24 h. After each experiment, the BiOBr@C hybrid decontamination material was filtered out and then put into a fresh Cr(VI) ion solution (5 mg / L). The Cr(VI) ion concentration (C0) was measured after 24 h. t , mg / L), through (C t After repeated use for 10 times, the decontamination efficiency of BiOBr@C hybrid decontamination material for Cr(VI) ions remained above 90%, indicating that BiOBr@C hybrid decontamination material has good decontamination stability.
Claims
1. Application of a porous carbon sphere-loaded bismuth oxyhalide hybrid material as a cleaning material in the photocatalytic degradation of heavy metal salts, characterized in that: The porous carbon sphere-supported bismuth oxyhalide hybrid material is prepared by a method comprising the following steps: Step 1: Add Tris-HCl buffer to deionized water at room temperature, then add silica microspheres and stir with ultrasonic stirring; Step 2: slowly add ammonia water and dopamine hydrochloride aqueous solution to the mixture obtained in step 1, stir to react, filter, wash and dry to obtain an intermediate product, i.e., dopamine-wrapped silica microspheres SiO2@PDA; Step 3: Under the protection of inert gas, using a tube furnace, the SiO2@PDA obtained in step 2 is heated to a certain temperature at a certain heating rate and kept warm; then the obtained product is added to a hydrofluoric acid aqueous solution, stirred at room temperature, filtered, washed and dried to obtain an intermediate product, i.e., carbon spheres; Step 4: at room temperature, add bismuth nitrate pentahydrate to the ethylene glycol solution of hexadecyltrimethylammonium bromide, stir for a certain period of time, then add the carbon spheres obtained in step 3, stir and ultrasonicate for a certain period of time; Step 5: adding potassium salt to the mixture obtained in step 4, stirring for a certain period of time, transferring the mixture to a high-pressure reactor, heating for reaction, filtering, washing and drying after the reaction is completed to obtain the target product; In step 2, the mass ratio of silica microspheres, ammonia water and dopamine hydrochloride aqueous solution is 1: 5: 500; wherein the mass fraction of ammonia water is 25%-28%, and the mass fraction of dopamine hydrochloride aqueous solution is 0.2%; In step 3, the heating rate of the tubular furnace is 5°C / min, the reaction temperature is 550°C, and the holding time is 2 h; In steps 4 and 5, the mass ratio of potassium salt, carbon spheres, bismuth nitrate pentahydrate and CTAB ethylene glycol solution is 1: 2.35-4.70: 2.92-8.23: 317.3; The potassium salt KX is selected from any one of potassium fluoride, potassium chloride, potassium bromide and potassium iodide.
2. The use according to claim 1, characterized in that: In step 1, the mass ratio of silica microspheres, Tris-HCl buffer and deionized water is 1: 7.88:
500.
3. The use according to claim 1, characterized in that: In step 3, the mass ratio of SiO2@PDA to the hydrofluoric acid aqueous solution is 1:100-200; wherein the mass fraction of the hydrofluoric acid aqueous solution is 20%.
4. The use according to claim 1, characterized in that: In step 5, the reaction temperature of the high-pressure reactor is 160-180° C., and the reaction time is 6-12 h.
5. The use according to claim 1, characterized in that: The chemical formula of the porous carbon sphere-loaded bismuth oxyhalide hybrid material is shown in the following formula (I): BiOX@C (I); In the formula (I), X is any one of fluorine, chlorine, bromine and iodine.
6. The use according to claim 1, characterized in that: The pH value of the catalytic degradation system was adjusted to 2.
Citation Information
Patent Citations
Preparation and application method of MoO2 (at) NHCS hollow structure material
CN115477374A